2022
DOI: 10.3390/app12041999
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Disorders in Pediatric Patients: A 20 Years’ Experience

Abstract: Salivary gland disorders are uncommon in children; they show a lower prevalence when compared to adults. The literature has a relative lack of information about the management and the different treatment protocols regarding these diseases. The aim of this research is to investigate the prevalence of both benign and malignant salivary gland disorders, focusing on diagnostic and therapy. An audit of patients diagnosed with salivary gland disorders was conducted from 2000 to 2020. 99 patients’ records were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Gellrich et al reported 146 pediatric patients with salivary gland disorders over a study period of 15 years [ 10 ]. Another study from Italy reported 99 children with salivary gland disorders over 20 years [ 11 ]. The majority of the studied patients were in the sixth decade of life which was similar to previous investigations [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gellrich et al reported 146 pediatric patients with salivary gland disorders over a study period of 15 years [ 10 ]. Another study from Italy reported 99 children with salivary gland disorders over 20 years [ 11 ]. The majority of the studied patients were in the sixth decade of life which was similar to previous investigations [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sialendoscopy is a procedure for the diagnosis and treatment of salivary obstructive and inflammatory diseases [ 5 , 6 , 7 , 8 ]. It can be performed under local or general anesthesia depending on the level of difficulty of the individual case.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment was either conservative or occasionally with aggressive surgical interventions such as Stensen’s duct ligation, superficial or total parotidectomy, and tympanic neurectomy [ 16 ]. The current treatment is shifted towards gland preservation with minimally invasive modalities such as sialendoscopy [ 1 , 17 ]. The latest has tremendously lowered the possibility of collateral damage, e.g., facial nerve injury or fibrosis of the salivary gland [ 4 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although considered rare, it is the second most common inflammatory disease of salivary glands in children. It is characterised by painful and intermittent swelling of the salivary glands that can be uni- or bilateral [ 1 , 2 ]. The condition is accompanied by overlying skin erythema, malaise, and pyrexia.…”
Section: Introductionmentioning
confidence: 99%